Tyrosine phosphorylation of HSC70 and its interaction with RFC mediates methotrexate resistance in murine L1210 leukemia cells. Issue 1 (1st February 2015) - Liu, Tuoen; Singh, Ratan; Rios, Zechary; Bhushan, Alok; Li, Mengxiong; Sheridan, Peter P.; Bearden, Shawn E.; Lai, James C.K.; Agbenowu, Senyo; Cao, Shousong; Daniels, Christopher K.
Highlights Novelty and impact: Heat shock cognate protein (HSC70) and reduced folate carrier (RFC) colocalizes and interacts with each other in L1210 cells. Tyrosine phosphorylation of HSC70 regulates the transportation of MTX into the cells via the HSC70-RFC system and contributes to MTX resistance in L1210 cells. The studies reveal a novel anti-cancer drug resistant mechanism at molecular levels.